PERSPECTIVES OF THE EUCHARISTIC CHANGE: A Systematic Study Based on the Wandlung Theology of Cardinal Kurt Koch with Special Reference to Jean-Luc Marion - Rappai, Jomon Mularikkal (Asian Horizons, 2019)
This dissertation is a humble attempt to understand the eucharistic transformation in its real sense. For, the word ‘transubstantiation’ is used to explain the eucharistic transformation that is difficult for a simple believer to comprehend, because of its complexity, its relation to metaphysics, dogmatically defined nature, and an inappropriate interpretation in the postmodern period. As history and philosophy are sources in theologicalresearch, I have outlined my work in the format of “eye of history, eye of philosophy and a brain of faith.”